Jejaring Radio Swasta Sebagai Inovasi Merebut Pasar - Moh. Zaenal Abidin Eko Putro; Ade Haryani (Jurnal Komunikasi, 2021)
In line with the growth of digital technology, according to Nielsen's survey (2020), 67 percent of netizen listening to music or radio through sharing platforms of social media such as YouTube and Dailymotion. However, the existence of analog based commercial radio remains unchanged. Nielsen's survey finds the tendency of the millennial generation to listen to the radio increased, especially during weekend. To prove the Nielsen’ finding, this article tries to uncover the strategy of private radio in attracting their listeners by offering network system in their broadcasting service. By using qualitative methods, this study compares the characteristics of the networked radio stations, namely KBR radio and Etnikom radio network, and their endeavor to maintain the network. The research shows that KBR is more focused on news network, while Etnikom is more tended to the ownership network. However, those radios show the uniqueness of innovation during the era of the current media competition.Keywords: broadcasting program, KBR and Etnikom, networking, private radio.